1491. Mycoplasma genitalium: A Concordance Study in Heterosexual Partnerships at Risk for Chlamydial Infection. (26th November 2018) - Younas, Mariam; Fife, Kenneth; Williams, James; Batteiger, Byron E
Abstract: Background: Mycoplasma genitalium (MG) causes symptomatic nonchlamydial, nongonococcal urethritis in men, and cervicitis, pelvic inflammatory disease and infertility in women. We aimed to determine: prevalence and concordance of MG infection within heterosexual partnerships; MG detection by sample site in infected subjects; symptom association with MG infection; frequency of co-infection with Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and Trichomonas vaginalis (TV); and risk factors associated with MG infection and concordance. Methods: Data from two partnership studies were combined; both enrolled sexually active heterosexual couples between the ages of 14–24 years who were at high risk for CT, between April 10, 2000 and September 29, 2003 at a sexually transmitted infection (STI) clinic in Indianapolis, IN. MG was detected by nucleic acid amplification from specimens stored at −70°C for up to 48 months. MG was sought in urine and urethra in men and urine, vagina, and cervix in women. Symptoms evaluated were dysuria, discharge in men and discharge, dysuria, abdominal pain in women. Symptom association with MG infection was analyzed by Chi-square test and logistic regression was used for associations of demographic, behavioral and biologic factors with MG concordance. Results: Microbiologic data were available from 200 men and 217 women, and demographic information from 188 men and 201 women in partnerships. 43/217 dyads contained an individual with MG infection, and both individuals were infected in 11/43 (26%) partnerships (concordant). In men and women MG detection was highest in urine (10%, 9%) specimens. Prevalence of MG was 14% in women and10% in men. Most infected men (79%) and women (62%) were African American. Mean age at first sex was 14 years for both genders. CT was the most frequent co-infection in both MG infected men (32%) and women (52%). MG infection without co-infection was associated with penile discharge in men (57%) P = 0.18. No symptoms in women were indicative of MG infection, and no demographic, behavioral or biologic factors were statistically associated with MG concordance. Conclusion: The prevalence of MG was substantial. Concordance in partnerships was 26%, less than observed with CT ( 70%) in this study. Our study is limited due to small numbers of subjects with MG infection. Disclosures: All authors: No reported disclosures.